Analysis of the Effectiveness of Employee Performance in Improving Public Services at the Bagan Sinembah Sub-District Office, Rokan Hilir Regency, Riau Province - Fenny Clara Saskia Manalu; Maksum Syahri Lubis; Rudi Salam Sinaga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to find out the Effectiveness of Employee Performance in Improving Public Services at the Bagan Sinembah Sub-District Office, Rokan Hilir Regency. This study used qualitative approach. Based on the results of research and discussion on Employee Work Effectiveness in Improving Public Services at the Bagan Sinembah District Office, Rokan Hilir Regency, Riau Province. The motivation here is defined as a performance of leaders and employees towards work situations in their agency environment, those who perform positively on their work situations will show high work motivation, this is also very supportive in creating enthusiasm and increasing Performance Effectiveness.Employees in Improving Public Services at the Bagan Sinembah Sub-District Office, Rokan Hilir Regency, Riau Province in each of the implementation of his duties and direction from the leadership to his subordinates can also create productive cooperation to achieve the goals that have been set. The ability to carry out the work has been good and the quality of the work has also obtained maximum results, with the achievement of this effective performance Performance EffectivenessEmployees in Improving Public Services at the Bagan Sinembah Sub-District Office, Rokan Hilir Regency, Riau Province have been required to apply good management standards and have been assessed and verified by the institution entitled to provide certification. Technology here is related to the use of assistive devices in an organization, doing a job is certainly supported by adequate technology.Provision of information and technology facilities in Performance EffectivenessEmployees in Improving Public Services at the Bagan Sinembah Sub-District Office, Rokan Hilir Regency, Riau Province has improved with the existence of WIFI networks and other supporting facilities that really help in completing the work.